Task and Ego Orientation in Sport Questionnaire (TEOSQ): Psychometric Properties in Its Digital Version - Morales-Sánchez, Verónica Odilia; Pérez-Romero, Nuria; Franquelo, María Auxiliadora; Balaguer, Isabel; Hernández-Mendo, Antonio; Hernández-Mendo, Rafael Enrique (IOAP-MPDI, 2022)
The Task and Ego Orientation in Sport Questionnaire’s (TEOSQ’s) psychometric properties have been explored in previous studies but never in its digital version, which facilitates data collection. The objective of this study was to analyze the psychometric properties of the online TEOSQ by MenPas 1.0. The sample was composed of 2320 users (58.4% women; 41.6% men), between 18 and 65 years old (M = 25.27, SD = 7.39). The methods used were Confirmatory Factor Analysis (CFA) and invariance analysis from the original 13-item model. The CFA was corrected for all samples (CFI = 0.92–0.94, TLI = 0.93–0.95, RMSEA = 0.07, SRMR = 0.06; df = 64; Bollen-Stine Bootstrap p = 0.02–0.07): general sample (χ2 = 720.72, χ2/df = 11.26), women (χ2 = 496.85, χ2/df = 7.76), men (χ2 = 321.67, χ2/df = 5.03), individual sports (χ2 = 525.26, χ2/df = 8.21), and team sports (χ2 = 306.01, χ2/df = 4.78). The results also indicate optimal adjustments for invariance: convergent, discriminant and composite reliability validity. The study evidence demonstrates the adequate psychometric properties of the digital version. To conclude, considering the results obtained, the model shows a good psychometric fit for the sample in its online format. The principal limitations were computer failures, as well as that the large part of the sample were users between 20 and 25 years old, so the heterogeneity should be improved. The practical implications of this study could improve the efficacy of data collection in sports motivation using the online TEOSQ
Keywords: Psicometría; Achievement goals; Sport; Invariance; Psychometric properties